2013
DOI: 10.1182/blood-2013-02-486217
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell and macrophage chemokines CXCL1/CXCL2 control the early stage of neutrophil recruitment during tissue inflammation

Abstract: Key Points Mast cells contribute to early neutrophil recruitment. Mast cells and macrophages both make CXCL1 and CXCL2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
585
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 702 publications
(624 citation statements)
references
References 49 publications
31
585
3
5
Order By: Relevance
“…Interestingly, these investigators found that the production of CXCL1 from TRAMP-G2LG cancer cells reached ∼4 ng/ml, similar to the concentration of CXCL1 that inhibited ASMC migration in our study. These results suggest that, although known as a mediator of cell chemotaxis (16,17), at specific concentrations CXCL1 may act as a negative regulator of cell migration/invasion both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, these investigators found that the production of CXCL1 from TRAMP-G2LG cancer cells reached ∼4 ng/ml, similar to the concentration of CXCL1 that inhibited ASMC migration in our study. These results suggest that, although known as a mediator of cell chemotaxis (16,17), at specific concentrations CXCL1 may act as a negative regulator of cell migration/invasion both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 83%
“…Although primarily known as a potent inducer of neutrophil chemotaxis (16), CXCL1 was shown to induce cancer cell invasion (17) and endothelial (18) and epithelial cell migration (19). CXCL1 facilitates its signaling by binding to its putative receptor, the chemokine receptor CXCR2, although it also was found to bind to CXCR1, albeit with lower affinity (20).…”
mentioning
confidence: 99%
“…The most notable changes in the cells treated with the combination of LG268 and LPS compared with LPS alone were a 3-fold downregulation of CSF3 and a 2.5-fold decrease of CXCL2 and IL1b mRNA expression. These cytokines play important roles in inflammation: CSF3 in the production and function of granulocytes (30), CXCL2 in the recruitment of neutrophils (31), and IL1b in promoting the infiltration of inflammatory myeloid cells and in angiogenesis (32,33). A complete list of the inflammatory cytokines, chemokines, and their receptors that showed any detectable changes in the panel of 440 genes following treatment with LG268 are listed in Supplementary Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the expression of CXCL2, the chemokine mainly responsible for recruiting neutrophils, 13,14 was found to be increased in the skin lesion both at the early and late stages (Figures 5a and b). Accordingly, there was significantly increased numbers of neutrophils in the lesional skin of the patients with SSc compared with the normal skin of the health control.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the expressions of chemokines CXCL2 and CCL17 were shown to be induced in the skin lesion following implantation of minipumps with BLM (Figure 5b), which strongly supported the cellular infiltration of neutrophils and T cells in the skin lesion according to their preferential chemotactic ability. [13][14][15][16] Delivery of BLM by Skin-Embedded Osmotic Minipumps Induces Interstitial Lung Disease-Like Manifestation SSc is a systemic autoimmune disease with multiple organs involved, and ILD is one of the most significant complications in SSc. TGF-b1 is widely considered to have a central role in fibrosis.…”
Section: Delivery Of Blm By Skin-embedded Osmotic Minipumpsmentioning
confidence: 99%